E0450 Usefulness of the neutrophil to lymphocyte ratio in predicting complications in patients with acute myocardial infarction. (17th November 2010) - Yi, Lu; Qiang, Fu; Yi, Liu; Yang, Sheng; Peng, Wei
Abstract : Objective: To investigate the relationship between the neutrophil to lymphocyte ratio and the morbidity of AMI complications. Methods: A total of 218 patients with ST segment elevated myocardial infarction whose blood routines were obtained at the admission were studied. All cases were divided into two groups according to the neutropil to lymphocyte ratio of small to large size. Then we analysed the morbidity of AMI complications between the two groups. Results: The peak value of cardiac troponin I was higher in group B ((32.5±21.7) ng/ml and (56.8±39.4) ng/ml respectively, p<0.01). The incidences of arrhythmia (17.43% and 39.45%, p<0.01), heart failure (22.94% and 51.38%, p<0.01) and death (2.75% and 11.01%, p<0.05) were also higher in group B. The multivariate stepwise regression analysis showed that the neutrophil to lymphocyte ratio and the morbidity of AMI complications had certain correlation. Conclusions: The neutrophil to lymphocyte ratio is a reliable indicator that can predict morbidity of AMI complications.